LEGAL ASPECTS OF INVESTMENT IN THE FRAMEWORK IMT-GT SUB-REGIONAL ECONOMIC COOPERATION (INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE) IN INDONESIA - Sayid Fadhil (Badan Penerbit STIEPARI Press, 2023)
Investment activities have a critical role in increasing the growth of a country's trade flows, and conversely, an increase in trade activities will also encourage investment growth. All of these aim to increase economic growth. The agreement in cooperation in investment in the Sub-Regional, Regional, and Multilateral scope regulates the principles of cross-border investment between countries by